India, Sri Lanka and the SAARC region - Bajpai, Lopamudra Maitra, author.
1 online resource (xv, 200 pages)
Keywords: "This book examines the historical and socio-cultural connections across the SAARC region, with a special focus on the relationship between India and Sri Lanka. It investigates hitherto unexplored narratives of history, popular culture and intangible heritage in the region to identify the cultural parallels and intersections that link them together. In doing so, the volume moves away from an organised and authorised heritage discourse and encourages possibilities of new understandings and re-interpretations of cross-cultural communication and its sub-texts. Based on original ethnographic work, the book discusses themes such as cultural ties between India and Sri Lanka; exchanges between Arthur C. Clarke in Sri Lanka and Satyajit Ray in India; cultural connectivity reflected through mythology and folklore; the influence of Rabindranath Tagore on modern dance in Sri Lanka; introduction of the railways in Sri Lanka; narrative scrolls and masked dance forms across SAARC countries; Hindi cinema as the pioneer of cultural connectivity; and women's writing across South Asia. Lucid and compelling, this book will be useful for scholars and researchers of cultural studies, South Asian studies, cultural anthropology, sociology, popular culture, Cross-cultural communication, gender studies, political sociology, cultural history, diplomacy, international relations and heritage studies. It will also appeal to general readers interested in the linkages between India and Sri Lanka"--